Man or Monster? : The Trial of a Khmer Rouge Torturer - Hinton, Alexander Laban (Book collections on Project MUSE., 2016)
During the Khmer Rouge's brutal reign in Cambodia during the mid-to-late 1970s, a former math teacher named Duch served as the commandant of the S-21 security center, where as many as 20,000 victims were interrogated, tortured, and executed. In 2009 Duch stood trial for these crimes against humanity. While the prosecution painted Duch as evil, his defense lawyers claimed he simply followed orders. In 'Man or Monster?' Alexander Hinton uses creative ethnographic writing, extensive fieldwork, hundreds of interviews, and his experience attending Duch's trial to create a nuanced analysis of Duch, the tribunal, the Khmer Rouge, and the after-effects of Cambodia's genocide. Interested in how a person becomes a torturer and executioner as well as the law's ability to grapple with crimes against humanity, Hinton adapts Hannah Arendt's notion of the "banality of evil" to consider how the potential for violence is embedded in the everyday ways people articulate meaning and comprehend the world